LAYANAN KONSELING KELOMPOK DENGAN TEKNIK MODELING TERHADAP PERILAKU IMPULSIF PADA ANAK ADHD - Ria Eka Lestari; Bakhrudin All Habsy; Endang Pudjiastuti Sartinah; Budiyanto Budiyanto (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
Impulsive behavior is an action that is done spontaneously and suddenly, without careful consideration or possible consequences. Children with Attention Deficit Hyperactivity Disorder often act without thinking, have difficulty controlling their impulses, and often do risky things without considering the consequences. Group counseling services are a form of psychological therapy where a group of individuals meet regularly to discuss the problems they face with a counselor. Children with Attention Deficit Hyperactivity Disorder (ADHD) often have a tendency to imitate the behavior of individuals around them. Therefore, modeling techniques are considered suitable for use in group counseling, because this technique allows group members to learn through observation and imitation of behavior exemplified by the counselor or other members. The application of group counseling using modeling techniques is important to study in relation to controlling impulsive behavior in children with ADHD. This study aims to investigate the effectiveness of group counseling with the modeling method in reducing impulsive behavior in children with ADHD, using a quantitative approach through a literature review. The results of the study indicate that: (1) Group counseling approach through modeling techniques can be a way of intervention for children with ADHD, and (2) this technique is effective in suppressing impulsive behavior in children with ADHD.